Vanadium-Doped Bi2S3@Co1−xS Heterojunction Nanofibers as High-Capacity and Long-Cycle-Life Anodes - Haomiao Yang; Lehao Liu; Zhuoheng Wu; Jinkui Zhang; Chenhui Song; Yingfeng Li (Energies)
Lithium-ion batteries (LIBs) are considered one of the most important solutions for energy storage; however, conventional graphite anodes possess limited specific capacity and rate capability. Bismuth sulfide (Bi2S3) and cobalt sulfide (Co1−xS) with higher theoretical capacities have emerged as promising alternatives, but they face challenges such as significant volume expansion during electrochemical cycling and poor electrical conductivity. To tackle these problems, vanadium was doped into Bi2S3 to improve its electronic conductivity; subsequently, a vanadium-doped Bi2S3 (V-Bi2S3)@Co1−xS heterojunction structure was synthesized via a facile hydrothermal method to mitigate volume expansion by the closely bonded heterojunction interface. Moreover, the built-in electric field (BEF) created at the heterointerfaces can significantly enhance charge transport and facilitate reaction kinetics. Additionally, the nanofiber morphology of the V-Bi2S3@Co1−xS heterojunction structure further contributed to improved electrochemical performance. As a result, the V-Bi2S3 electrode exhibited better electrochemical performance than the pure Bi2S3 electrode, and the V-Bi2S3@Co1−xS electrode showed a significantly enhanced performance compared to the V-Bi2S3 electrode. The V-Bi2S3@Co1−xS heterojunction electrode displayed a high capacity of 412.5 mAh g−1 after 2000 cycles at 1.0 A g−1 with high coulombic efficiencies of ~100%, indicating a remarkable long-term cycling stability.